A CASE REPORT: ENHANCING TARSAL AND MUSCULAR SUPPORT FOR ECTROPION CORRECTION IN TESSIER 3 AND 5 FACIAL CLEFT - Adifitrian, Teuku; Hartono, Hendra Tri; Garnasih, Agustina Indah (Jurnal Rekonstruksi dan Estetik, 2023)
Highlights: The oblique facial cleft is an uncommon and intricate craniofacial anomaly characterized by a low occurrence rate and significant variability. The treatment is intricate and relies on the surgeon's expertise and discernment. Utilizing a combination of Tarsal Strip and Midface Lifting techniques could serve as an alternative approach to address ectropion by enhancing both tarsal and muscular support. Abstract: Introduction:  Facial cleft is a rare and challenging craniofacial malformation with a low incidence ranging from 0.75 to 5.4 per 1000 common cleft. Due to the high variance in its occurrence, good techniques have not been established yet. Case Illustration: In this case study, we present the medical history of a 45-year-old woman who previously underwent multiple surgeries for the reconstruction of her lower eyelid. The initial surgeries were performed to address a unilateral facial cleft classified as Tessier 3 and 5, utilizing ear cartilage grafts for the tarsal plate. However, she subsequently experienced complications, including ectropion, epiphora, and soft tissue deformities around her left eye. The goal of the current surgical intervention is to rectify the ectropion and enhance overall facial aesthetics for improved outcomes. Discussion: The primary objectives of this surgical techniques are to enhance the tarsal support through the tarsal strip technique and to provide muscle support using the mid-face lifting technique. Additionally, we removed the scar and excess tissue from the lower lid to adjust the tarsal's proper length. These methods aim to address the ectropion and prevent its recurrence. Conclusion: This combination of techniques can be a potential alternative for rectifying ectropion by reinforcing both tarsal and muscular support structures.